Accurate and efficient evaluation method of moments matrix based on a generalized analytical approach - Liu, Z. H. (2013)
Based on an analytical expression for the integration of the free-space Green's function involving any combination of basis and test functions, an accurate and highly e±cient method to determine the Method of Moments matrix has been developed. A full analytical expression is obtained through direct integration of the Taylor's series expansion of the free-space Green's function. Based on the distance between the source and observation points, a criterion is established to reduce the full expression to a much-simplified expression, which speeds up the computational efficiency to fill up the Method of Moments matrix without compromising the solution accuracy.